2012
DOI: 10.1016/j.ajpath.2011.10.017
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine A2A Receptor Ligation Inhibits Osteoclast Formation

Abstract: Adenosine is generated in increased concentrations at sites of injury/hypoxia and mediates a variety of physiological and pharmacological effects via G protein-coupled receptors (A(1), A(2A), A(2B), and A(3)). Because all adenosine receptors are expressed on osteoclasts, we determined the role of A(2A) receptor in the regulation of osteoclast differentiation. Differentiation and bone resorption were studied as the macrophage colony-stimulating factor-1-receptor activator of NF-κB ligand formation of multinucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
146
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 89 publications
(159 citation statements)
references
References 61 publications
12
146
1
Order By: Relevance
“…These results are in agreement with some previous investigations [16,17] but differ from others. For example, A 2A receptor agonists have been shown to both inhibit [33] and stimulate [25] the formation and activity of osteoclasts. Kara and colleagues [51] found that A 1 receptor antagonists decreased osteoclast formation and resorption.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results are in agreement with some previous investigations [16,17] but differ from others. For example, A 2A receptor agonists have been shown to both inhibit [33] and stimulate [25] the formation and activity of osteoclasts. Kara and colleagues [51] found that A 1 receptor antagonists decreased osteoclast formation and resorption.…”
Section: Discussionmentioning
confidence: 99%
“…However, more recent work has indicated that adenosine, acting through the A 2A receptor, may stimulate the formation of osteoclasts from human peripheral blood cells [25]. In contrast, Mediero et al (2012) [33] found that A 2A receptor agonists inhibited mouse osteoclast formation in vitro. Blockade or deletion of the A 1 receptor has additionally been reported to reduce the formation of mouse osteoclasts in culture [23]; however, the same group also found that stimulation of the A 1 receptor had no effect on mouse osteoclasts [34].…”
Section: Introductionmentioning
confidence: 99%
“…ATP released through P2X7 receptors acts as the major source of adenosine that enhances mature osteoclast function via A 2A receptors [273]. However, a later study showed that adenosine, acting through A 2A receptors, inhibited osteoclast differentiation [285]. Thus, the authors suggested that adenosine may regulate bone turnover under conditions when levels are elevated [285].…”
Section: P1 Receptors Adenosine and Osteoclastsmentioning
confidence: 99%
“…However, a later study showed that adenosine, acting through A 2A receptors, inhibited osteoclast differentiation [285]. Thus, the authors suggested that adenosine may regulate bone turnover under conditions when levels are elevated [285]. A 2A receptor activation has also been shown to prevent the osteolysis that occurs during prosthesis loosening with particle-induced inflammation, a common cause of joint implant failure [286].…”
Section: P1 Receptors Adenosine and Osteoclastsmentioning
confidence: 99%
“…Since bone remodelling is orchestrated by osteoblasts, osteoclasts and osteocytes, other studies from Cronstein's laboratory [8][9][10][11] have recently demonstrated a role for the A1 and A2A ARs in osteoclast differentiation and function, again using KO mouse as study models. Furthermore, there is much recent data on the role of adenosine in joint disease such as arthritis (see e.g., [12,13]).…”
Section: Commentarymentioning
confidence: 99%